MODERASI BERAGAMA DI KEMENTERIAN AGAMA: STUDI PADA PEMAHAMAN GURU MADRASAH DI KABUPATEN BONE - Haslinda, Haslinda (Adaara: Jurnal Manajemen Pendidikan Islam, 2022)
This research discusses Religious Moderation in the Ministry of Religious Affairs (A Study on the Understanding of Madrasa Teachers in Bone District). The sub-problems are what the concept of religious moderation in the Ministry of Religious Affairs of Bone District is and how the understanding and implementation of religious moderation of madrasa teachers in Bone District is. This research is a field research. The research method is a qualitative method using a pedagogical, psychological, and sociological approach. The data collection methods are observation, interview-questionnaire, and documentation. Furthermore, the technique of data processing and data analysis is using the data triangulation method. The results showed that: First, the concept of religious moderation in the Ministry of Religious Affairs of Bone District has the indicators, namely love for the homeland, high tolerance, anti-violence, and accommodating to culture. The references for religious moderation at the Ministry of Religious Affairs of Bone District are in the form of perspectives, attitudes, and behaviors that always take a position in the middle, always act fairly, and are not extreme in religion. Second, the understanding of madrasa teachers on religious moderation in Bone District is still different based on the madrasa unit. At MAN 1 Bone, the teachers agree and understand well the concepts, dimensions, and indicators of religious moderation, as well as at MTsN 1 Bone, but there are still teachers who do not understand religious moderation, especially at MI DÄrul Hikmah. Meanwhile, the implementation of religious moderation in madrasas can be done through three strategies, namely insertion, optimizing the approach, and organizing special programs on religious moderation. As a finding of the theory built on this research, the more programs that specifically focus on religious moderation, the better oneâ€™s religious understanding and attitude.